Buckling Analysis of Porous Functionally Graded Plates - Gupta, Anil Kumar; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
This study investigated the buckling behavior of Porous Functionally Graded Material (PFGM) plates. The present model assumes unevenly distributed porosity along the plate thickness and the use of the novel hyperbolic shear deformation functions and hyperbolic tangent and secant thickness stretching functions. In the present work, a porous Functionally Graded (FG) plate was analyzed by the principle of virtual work in order to understand the buckling behavior under uniaxial and biaxial compressive loading. The Rayleigh quotient method was applied to find the critical buckling load. The mesh convergence was investigated on a Finite Element (FE) model, and the accuracy of the results was compared with the prior research. The results of the proposed model match reasonably well with the ones of the published literature. Thorough parametric studies were performed to investigate the effect of porosity on the critical buckling load of the PFGM plate.